2019
DOI: 10.3390/su11216128
|View full text |Cite
|
Sign up to set email alerts
|

Design of Urban Rail Transit Network Constrained by Urban Road Network, Trips and Land-Use Characteristics

Abstract: In the process of urban rail transit network design, the urban road network, urban trips and land use are the key factors to be considered. At present, the subjective and qualitative methods are usually used in most practices. In this paper, a quantitative model is developed to ensure the matching between the factors and the urban rail transit network. In the model, a basic network, which is used to define the roads that candidate lines will pass through, is firstly constructed based on the locations of large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Koźlak, 2013;Button, 2017), civil engineers (e.g. de Azevedo Isidoro et al, 2017Chai et al, 2019), as well as journalists (e.g. Wolmar, 2007), and a large group of enthusiasts (e.g.…”
Section: Study Objectives Source Materials and Research Methodsmentioning
confidence: 99%
“…Koźlak, 2013;Button, 2017), civil engineers (e.g. de Azevedo Isidoro et al, 2017Chai et al, 2019), as well as journalists (e.g. Wolmar, 2007), and a large group of enthusiasts (e.g.…”
Section: Study Objectives Source Materials and Research Methodsmentioning
confidence: 99%
“…Gutiérrez-Jarpa et al [16] considered the detailed passenger access or egress time between nodes and stations in the model. Chai et al [23] studied the urban rail transit network design problem using a neighborhood search algorithm and applied a utility function for passenger path selection. Zhou et al [24] solved the line-planning problem with passenger path assignment by using commercial linear programming solvers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…//Reduced cost for each traveler (23) for p ∈ P do (24) Calculate the reduced cost S p , with the new path. (25) if S p < 0 and NewPath not in PathPool then (26) PathPool � PathPool ∪ New Path.…”
mentioning
confidence: 99%
“…Peeters and omas [10] show that the network structure has a significant impact on facility siting. Chai et al [11] proposed a valuable model to efficiently define candidate lines for safe pass through of rails. In the model of Fielbaum et al [12] four transit structures are suggested for safe and speedy transportation.…”
Section: Introductionmentioning
confidence: 99%